(3YbO GdLeGf aj JGQjN Cgd GdReGfs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s ((3GdeOQSI GdYHjOjI HGdbGgQI s)
(3ChdgG (B:s
(3jHJOF HMhGOK SfI (B579 s
(3BNQgG (B:s
(3jfJgi HBNQ SfI (B620 s
(3gfGc CLRGA CNQi djSJ HNW GdeDda ef SfI (B2374 (3Edi SfI (B2396s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B184 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1150s
Keywords: (3GdJGQjNs